Analisis Hubungan Dinamis Antara Foreign Capital Inflows dan Pasar Saham di Indonesia - M. Rasyidin (Universitas Darussalam Gontor, 2015)
We conduct an analysis of the impact of foreign capital inflows on the stock market development in Indonesia. This study hypothesizes that there is long-term cointegration relationship between foreign capital inflows and stock market development in Indonesia. The empirical analysis was presented by time series model. The time period of analysis is quarter time series data from 1999:q1 to 2010:q4 in Indonesia. This paper examines the impact of foreign capital inflows on stock market development in Indonesia. In VAR model, the integration and Cointergration analysis suggested that there is a long run relationship among the factors. The results indicate that foreign capital inflows significantly influence the development of stock market in Indonesia. We found that there is a long-run relationship between foreign capital inflows and stock market development in Indonesia. The error correction term is statistically significantly at 10 percent level.